Mapping the landscape of mycological organizations in europe: where citizen science meets professional mycology - Danny Haelewaters; Dilzara Aghayeva; Sergio de-Miguel; Polina Degtjarenko; Glen Dierickx; Bálint Dima; Paul S. Dyer; Vasco Fachada; Sergio Enrico Favero-Longo; Nina V. Filippova; Montserrat Ganado; Susana C. Gonçalves; et al. (Biodiversity and Conservation, 2026)
Fungi have been used by humans since prehistoric times. Informal structures or groups for knowledge exchange regarding mushrooms and lichens probably existed for ages. Only recently, mycological activities have been structured in formal organizations. And where until a few centuries ago there were only learned societies and naturalists’ clubs, nowadays also mycological societies and citizen scientists have joined the landscape. However, the history of mycological organizations and activities in Europe is difficult to track. Here, we initiated two surveys to characterize the current landscape of mycological organizations focused on fungal diversity across Europe and to collate citizen science activities mapping fungi. The surveys were shared on social media and sent to mycologists in 49 countries in Europe. Responses of the surveys allowed us to present the history, geographical distribution, and structure of mycological organizations in Europe as well as their types of activities, including the publication of journals and magazines, the organization of meetings and educational initiatives, and citizen science projects. In addition to the surveys, local mycologists presented expert knowledge for a more comprehensive overview. Our data show that the mycological landscape in Europe is diverse and heterogeneous. We discuss ways to overcome economic, cultural, and linguistic barriers towards better integration of mycological communities, activities, and data in Europe. Mycological societies focused on studying fungal diversity can be leveraged towards common goals that include raising public awareness, data integration, uniting academics and non-academics, and developing common standards for research and communication.